Numerical Integration Implementation Using Trapezoidal Rule Method To Calculate Aproximation Area Of West Java Province - Wida Nurul Fauziyah; Athaya Zahrani Irmansyah; Sri Purwani (International Journal of Quantitative Research and Modeling, 2021)
An area can be shaped into a regular shape or an irregular shape. There is an area of irregular shape which is restricted by an unknown function, to determine that area must use a numerical integration. One of numerical integration methods is Trapezoidal Rule by replacing (????) with an integral approach function which can be evaluated, then let the (????) approximated by a linear polynomial in the certain interval, denoted as closed interval . This study is going to calculate the area of West Java Province by using this method with several different number of partitions in each quadrant such as, 9 partitions, 11 partitions, and 36 partitions in for different quadrants. This study provides the final result of the approximate area which will be compared with the actual area based in the error of result. The main finding is the approximate total area will be closer to the actual area followed by the increasing number of partitions.